2023
DOI: 10.31219/osf.io/y79u5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Megastudy testing 25 treatments to reduce anti-democratic attitudes and partisan animosity

Abstract: Deep partisan conflict in the mass public threatens the stability of American democracy. We conducted a megastudy (n=32,059) testing 25 interventions designed by academics and practitioners to reduce Americans’ partisan animosity and anti-democratic attitudes. We find nearly every intervention reduced partisan animosity, most strongly by highlighting sympathetic and relatable individuals with different political beliefs. We also identify several interventions that reduced support for undemocratic practices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Then, there is the Crowdsourcing Hypothesis Tests collaboration, which assigned 15 research teams to each design a study targeting the same hypothesis, varying in methods . Moreover, there is a recent trend in behavioral science to run "megastudies," in which researchers test a large number of treatments in a single study in order to increase the pace and comparability of experimental results (Milkman et al, 2021(Milkman et al, , 2022Voelkel et al, 2022).…”
Section: How Do Integrative Experiments Differ From Other Recent Inno...mentioning
confidence: 99%
“…Then, there is the Crowdsourcing Hypothesis Tests collaboration, which assigned 15 research teams to each design a study targeting the same hypothesis, varying in methods . Moreover, there is a recent trend in behavioral science to run "megastudies," in which researchers test a large number of treatments in a single study in order to increase the pace and comparability of experimental results (Milkman et al, 2021(Milkman et al, , 2022Voelkel et al, 2022).…”
Section: How Do Integrative Experiments Differ From Other Recent Inno...mentioning
confidence: 99%
“…Indeed, they show that left-right divisions can be partially overcome through psychological processes that motivate participants to preserve the American democratic system. And other recent work has shown that a variety of strategies can reduce affective polarization (Voelkel et al 2023).…”
Section: “Us” Versus “Them”mentioning
confidence: 99%
“…Graham and Svolik (2020) find that partisans prefer candidates from their own party even if they violate norms such as electoral fairness, checks and balances, and/or civil liberties. 9 In their mega-study, Voelkel, Stagnaro, et al (2023) manipulated affective polarization (in nearly two dozen distinct ways) such that it decreases; they find the manipulations lead to less support for undemocratic candidates from respondents’ parties (e.g., candidates who would not accept the results of elections they lose). On the other hand, Broockman, Kalla, and Westwood (2022) find that inducing higher levels of affective polarization, via an interpersonal trust game, does not increase partisan loyalty, does not decrease accountability evaluations (e.g., assessing candidates based on whether their votes agreed with the respondent’s positions), and does not decrease support for democratic norms.…”
Section: The Political and Democratic Consequences Of Affective Polar...mentioning
confidence: 99%
“…Political violence can be thought of as a democratic norm violation insofar as it constitutes a substitution of violence for politics. Yet multiple studies find either no or a negative relationship between affective polarization and support for partisan or political violence (e.g., Harteveld, Mendoza, and Roodujin 2022; Mernyk et al 2022; Voelkel, Chu, et al 2023; Voelkel, Stagnaro, et al 2023; although see Bankert 2024). For instance, prior to the November 2020 election, Druckman et al (2024) asked a panel of respondents, whose affective polarization had been measured a year and a half earlier, how likely they would be to break the law without engaging in violence (e.g., defacing public property) and to engage in violence if the candidate from the opposing party won a contested election.…”
Section: The Political and Democratic Consequences Of Affective Polar...mentioning
confidence: 99%